Glioma cells remotely promote erythropoiesis as a self‐expanding strategy of cancer stem cells. (9th December 2021) - Aimaitijiang, Alapati; Tabu, Kouichi; Wang, Wenqian; Nobuhisa, Ikuo; Taga, Tetsuya
Abstract: Cancer stem cells are a promising target for cancer eradication due to their responsibility for therapy‐resistance and cancer recurrence. Previously, we have demonstrated that glioma stem cells (GSCs) recruit and induce the differentiation of bone marrow (BM) monocytes into tumor‐infiltrating macrophages, which phagocytose hemorrhaged erythrocytes and store GSC‐beneficial iron in mouse xenografts, suggesting a self‐expanding strategy of GSCs that exploits host hematopoiesis of myeloid cells. However, it remains unclear whether a self‐advantageous effect of GSCs also occurs on erythroid cells during glioma development. Here, we found that, in the primary cultures of mouse fetal liver proerythroblasts (proEs), conditioned media prepared from glioma cells including patient‐derived glioblastoma (GBM) cells significantly facilitated the differentiation of proEs into erythroblasts. Importantly, in‐vivo erythroid analysis in intracranially GSC‐transplanted mice showed an enhanced erythropoiesis in the BM. In addition, the sphere forming ability of patient‐derived GBM cells was significantly suppressed by hypoxia treatment and iron chelation, suggesting higher demands of GSCs for oxygen and iron, which may be supplied by GSCs‐ and their progeny‐induced erythrocyte production. Our findings provide a new insight into survival and expanding strategies of GSCs that systemically exploit host erythropoiesis. Abstract : Secreted factors from glioma cells promote erythroid differentiation. Glioma induces enhanced erythropoiesis in bone marrow of tumor‐bearing mice, even in the absence of anemia. Increasing erythrocytes in the tumor microenvironment may potentially supply oxygen and iron to foster glioma progression.